Incidence of Emergency Department Visits for ST-Elevation Myocardial Infarction in a Recent 6-Year Period in the United States - Ward, Michael J. (Am J Cardiol, 2014)
The incidence and longitudinal trends of patients with ST-elevation myocardial infarction (STEMI) presenting to U.S. emergency departments (EDs) are currently unknown. Efforts to use effective treatments for cardiovascular disease may decrease ED STEMI presentation. We conducted a descriptive epidemiological analysis of STEMI visits to EDs between 2006 and 2011 using the Nationwide ED Sample (NEDS), the largest source of U.S. ED data, to determine the incidence of patients with STEMIs presenting to U.S. EDs. We included adult ED visits with an ICD-9CM diagnosis of STEMI and calculated incidence rates for STEMI ED visits using U.S. census population data. Incidence calculations were stratified by age group, geographic region, and year. From 2006–2011, there was a mean of 258,106 STEMIs presenting to EDs per year, declining from 300,466 in 2006 to 227,343 in 2011. Incidence of ED STEMI visits per 10,000 adults declined from 10.1 (95% CI 9.8, 10.8) in 2006 to 7.3 (95% CI 6.8, 7.8) in 2011. The Midwest had the highest rate of ED STEMIs at 10.0 (95% CI 9.2, 10.8) and the West had the lowest with 6.6 (95% CI 6.1, 7.0). The incidence of STEMI decreased for all age groups during the study period. In conclusion, we report the first national estimates of STEMI presentation to U.S. EDs, which demonstrate decreasing incidence across all age groups and all geographic regions between 2006 and 2011. A declining STEMI incidence may affect the quality and timeliness of STEMI care. Continued national STEMI surveillance is needed to guide healthcare resource allocation.